Review on liquid chromatographic analysis of colchicine in the forensic and medical perspective - Krishna, Rohith; Shivankar, Bhavana (Toxicologie Analytique et Clinique, 2021)
Colchicine is a tricyclic alkaloid extracted from the family of plants called Colchicaceae. Colchicine is pharmacologically active and works as an anti-mitotic agent. The alkaloid has a narrow therapeutic index, and a slight increase in colchicine concentration can lead to toxicity, and an overdose can be fatal to the individual. This nature of the alkaloid has made the scientific community interested in the analysis of colchicine. This critical review mainly comprises an analytical overview of the extraction and the liquid chromatographic (LC) analysis of colchicine in the field of forensic and medical toxicology. The prominent extraction techniques, detectors, and liquid chromatographic parameters favorable for colchicine estimation have been discussed in this paper. This review has covered the relevant research works within a timeline of two decades based on the scope of the literature and the scientific importance.

Synergistic effect of lactam and pyridine nitrogen on polysulfide chemisorption and electrocatalysis in lithium sulfur batteries - Javaregowda, Bharathkumar H.; Kargude, Radhakisan; Birajdar, Sarika; Shivankar, Bhavana; Krishnamurty, Sailaja; Jones, Lathe A.; Caruso, Rachel A.; Krishnamoorthy, Kothandam (ACS APPLIED MATERIALS & INTERFACES, 2024)
Keywords: Li-S battery; phenyl-diketopyrrolopyrrole; pyridine-diketopyrrolopyrrole

Dual agonist/antagonist modulation of α9-containing nicotinic acetylcholine receptors by 2-ammoniumethyl ethers of stilbenol and stilbenol analogues - Giraudo, Alessandro; Tae, Han-Shen; Hung, Andrew; Richter, Katrin; Shivankar, Bhavana; Armano, Edoardo; Grau, Veronika; Pallavicini, Marco; Adams, David J.; Bolchi, Cristiano (Journal of Medicinal Chemistry, 2025)
2-(Cyclohexyldimethylammoniumethyl)ether of 4-stilbenol (2), and its styryl-modified analogues 21 and 22, were identified as lead compounds from a series targeting human alpha 9 alpha 10, alpha 9, and alpha 7 nicotinic acetylcholine receptors (nAChRs). Compounds 2 and 21 exhibited potent, and subtype-selective modulation of alpha 9-containing receptors, with low nanomolar IC50 values and dual agonist/antagonist activity in a concentration-dependent manner. In contrast, compound 22 acted as a selective, pure antagonist. Molecular dynamics (MD) simulations of compound 21 supported a concentration-dependent allosteric mechanism, with orthosteric binding at low concentrations and vestibular site interaction at higher levels. In a human monocytic cell line, all three compounds inhibited ATP-induced IL-1 beta release at nanomolar concentrations. These findings identify alpha 9 alpha 10-selective ligands as promising scaffolds for the development of nonopioid analgesics and immunomodulators, with favorable selectivity over alpha 7 nAChRs to minimize CNS-related side effects.